Mitochondrial Dysfunction in Alzheimer’s Disease and the Rationale for Bioenergetics Based Therapies - Isaac G. Onyango; Jameel Dennis; Shaharyah M. Khan (2016)
Alzheimer's disease (AD) is a debilitating neurodegenerative disorder characterized by the progressive loss of cholinergic neurons, leading to the onset of severe behavioral, motor and cognitive impairments. It is a pressing public health problem with no effective treatment. Existing therapies only provide symptomatic relief without being able to prevent, stop or reverse the pathologic process. While the molecular basis underlying this multifactorial neurodegenerative disorder remains a significant challenge, mitochondrial dysfunction appears to be a critical factor in the pathogenesis of this disease. It is therefore important to target mitochondrial dysfunction in the prodromal phase of AD to slow or prevent the neurodegenerative process and restore neuronal function. In this review, we discuss mechanisms of action and translational potential of current mitochondrial and bioenergetic therapeutics for AD including: mitochondrial enhancers to potentiate energy production; antioxidants to scavenge reactive oxygen species and reduce oxidative damage; glucose metabolism and substrate supply; and candidates that target apoptotic and mitophagy pathways to remove damaged mitochondria. While mitochondrial therapeutic strategies have shown promise at the preclinical stage, there has been little progress in clinical trials thus far.